Determination of The Effect of Salicylic Acid Application on Salinity Stress at Germination Stage of Bread Wheat - Melikşah YILMAZ; Ferhat KIZILGECI; Nihan TAZEBAY ASAN; Ufuk ASAN; Asif IQBAL; Muhammad Aamir IQBAL (Yüzüncü Yil Üniversitesi Tarim Bilimleri Dergisi, 2022)
Under changing climate, abiotic stresses especially salinity have posed serious threats to modern crop production systems of staple crops and chemo-priming with salicylic acid offers a promising remedy. The present study aimed at ameliorating the adverse effects of salt stress through optimization of salicylic acid (SA) for two bread wheat genotypes (DZ17-1 and Empire Plus). The trial was comprised of chemo-priming with different SA levels including 0, 0.5, and 1 mM applied to the seeds of bread wheat genotypes exposed to different salinity levels (0, 50, 100, 150, 200 mM NaCl). The response variables included germination indices, roots length, and weight along with seedling traits. The results revealed that increasing the level of salinity had a negative effect on both genotypes of wheat and all traits studied. The DZ17-7 genotype was found to be more tolerant to salt stress. Among SA concentrations, 1 mM imparted a significant influence on germination, root traits, and seedling parameters. Although SA showed positive effects in salt stress conditions in the study, further studies are needed to clarify the role of SA in providing stress tolerance of plants.